Service Excellent lembaga pendidikan di era pandemi Covid-19 - Rahmawati, Penny; Hidayati, Lina Nur; Darmawati, Arum; Gallen, Mahendra Ryansa (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2023)
Service excellent training for educational institutions of Yayasan Pendidikan dan Sosial Cendekia Bantul aims to improve the ability of teachers and foundation managers in providing excellent service to student stakeholders, parents, the community and the government.The method used in this service activity is in the form of lectures and practices. The implementation of community service activities lasted for 2 days online due to the Covid-19 pandemic conditions while still following strict health protocols to maintain health during the Covid-19 pandemic. The material provided is in the form of theory and practice on strategies to develop superior schools, excellent service, and standard operational procedures (SOPs). The results of this PPM activity show that participants can understand the training material well. During the activity, participants also gave positive responses to the material provided, especially in discussing case studies of excellent service to parents and making simple SOPs. The achievement of activity targets is measured using evaluation instruments on the clarity of PPM objectives, training benefits, implementation time, training materials and future program sustainability.